"It's about how much we can do, and not how little we can get away with": Coronavirus-related legislative changes for social care in the United Kingdom. (September 2020) - Vicary, Sarah; Stone, Kevin; McCusker, Pearse; Davidson, Gavin; Spencer-Lane, Tim
Abstract: The coronavirus pandemic, referred to here as Covid-19, has brought into sharp focus the increasing divergence of devolved legislation and its implementation in the United Kingdom. One such instance is the emergency health and social care legislation and guidance introduced by the United Kingdom Central Government and the devolved Governments of Wales, Scotland and Northern Ireland in response to this pandemic. We provide a summary, comparison and discussion of these proposed and actual changes with a particular focus on the impact on adult social care and safeguarding of the rights of citizens. To begin, a summary and comparison of the relevant changes, or potential changes, to mental health, mental capacity and adult social care law across the four jurisdictions is provided. Next, we critique the suggested and actual changes and in so doing consider the immediate and longer term implications for adult social care, including mental health and mental capacity, at the time of publication.several core themes emerged: concerns around process and scrutiny; concerns about possible changes to the workforce and last, the possible threat on the ability to safeguard human rights. It has been shown that, ordinarily, legislative provisions across the jurisdictions of the UK are different, save for Wales (which shares most of its mental health law provisions with England). Such divergence is also mirrored in the way in which the suggested emergency changes could be implemented. Aside from this, there is also a wider concern about a lack of parity of esteem between social care and health care, a concern which is common to all. What is interesting is that the introduction of CVA 2020 forced a comparison to be made between the four UK nations which also shines a spotlight on how citizens can anticipate receipt of services.